2013
DOI: 10.1182/blood-2012-11-466086
|View full text |Cite
|
Sign up to set email alerts
|

WT1 regulates murine hematopoiesis via maintenance of VEGF isoform ratio

Abstract: Mutations in theWilms tumor suppressor 1 (WT1) gene are as frequent in acutemyeloid leukemia (AML) as in nephroblastma and predict poor prognosis. However, the role of WT1 in hematopoiesis remains unclear. We show that Wt1-deficient mouse embryonic stem cells exhibit reduced hematopoietic potential caused by vascular endothelial growth factor A (Vegf-a)–dependent apoptosis of hematopoietic progenitor cells associated with overproduction of the Vegf-a120 isoform. We demonstrate that Wt1 promotes exon inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In contrast, our work shows a differential effect of individual WT1 isoforms on the internal, better characterized VEGF splice sites. Similar results were reported by Cunningham et al who showed that loss of WT1 expression in hematopoietic progenitor cells results in an abnormal profile of VEGF isoforms [42]. We did not evaluate which exon 8 was included, but since both WT1A and WT1D increase angiogenesis, it is unlikely that either isoform alone increases the use of exon 8b (which is antiangiogenic) over exon 8a.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, our work shows a differential effect of individual WT1 isoforms on the internal, better characterized VEGF splice sites. Similar results were reported by Cunningham et al who showed that loss of WT1 expression in hematopoietic progenitor cells results in an abnormal profile of VEGF isoforms [42]. We did not evaluate which exon 8 was included, but since both WT1A and WT1D increase angiogenesis, it is unlikely that either isoform alone increases the use of exon 8b (which is antiangiogenic) over exon 8a.…”
Section: Discussionsupporting
confidence: 65%
“…In studying the relationship between WT1 and vEGF, an important growth factor in cancer, loss of WT1 results in increased abundance of isoform vEGF-a120, while transfection of WT1 results in exon inclusion and loss of the 120 isoform. This demonstrates that WT1 is essential for controlling the splicing of vEGF-a (48). studies of the vEGF-b isoform have also shown alteration of splicing patterns with WT1 manipulation.…”
Section: Role Of Transcription Factor Binding On Splicingmentioning
confidence: 74%
“…This aspect of WT1 controlled paracrine or intercellular signaling, is furthermore highlighted by reports on the regulation of VEGF-A via WT1 [132,133]. More recent studies identified the essential role of WT1 in RNA splicing of VEGF isoforms [134,135]. For example, it was demonstrated that WT1 mutant cells failed to repress the splicing-factor kinase SRPK1 resulting in altered splicing of VEGF isoforms, turning cells overall in a proangiogenic state [134].…”
Section: Regulatory Network Of Glomerular Development -Is Transcriptmentioning
confidence: 93%